2014
DOI: 10.1007/s00417-014-2738-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokines as biomarkers for age-related macular degeneration

Abstract: Elevation of IL-1α, IL-1β, IL-4, IL-5, IL-10, IL-13, and IL-17 in the serum of AMD patients supports the hypothesis of AMD as an inflammatory disease. Patients with high IL-17 and TNF-α serum levels were more likely to have a favourable course under VEGF therapy. These cytokines may be used as easy-to-obtain biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 20 publications
1
89
1
3
Order By: Relevance
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24]. This study demonstrated that AMD patients also presented an imbalance in the composition of CD4 + T …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24]. This study demonstrated that AMD patients also presented an imbalance in the composition of CD4 + T …”
Section: Discussionmentioning
confidence: 56%
“…Th17 cells also secrete TNF in addition to IL-17 and are implicated in multiple inflammatory mechanisms [15]. Interestingly, AMD patients presented increased serum levels of proinflammatory cytokines, including IL-1β, TNF, and IL-17 [16]. Therefore, in this study, we examined the Th1 and Th17 cells in AMD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an association between two single nucleotide polymorphisms in the IL-17 gene, rs2275913G/A and rs3748067C/T and AMD was reported 42 . IL-17 and TNF-α have been observed at higher concentrations in AMD patients and may be linked to a more favorable response to anti-VEGF therapy 43 . Altered DNA methylation of the IL17RC promoter has been observed in AMD patients leading to an elevated expression of its protein and messenger RNA in peripheral blood and affected parts of the retina and choroid 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AMD have increased plasma levels of inflammatory cytokines such as IL-1α, IL-1β, IL-4, IL-5, IL-13, and IL-17 [35]. The strongest links with disease are related to the pro-inflammatory cytokines IL-1, IL-6, and TNF-α, which are released from the choroid of patients with AMD and can immune-mediated retinal damage [17].…”
Section: Amd and Serological Biomarkersmentioning
confidence: 99%